DEVELOPMENT OF SOLAR-POWERED FISHING BOATS WITH LEAK THREAT SENSOR SYSTEM: A SUSTAINABLE SOLUTION FOR INDONESIAN FISHERMEN - Muzaki, Imam; Wijaya, Mirza Mahbub; Dewadi, Fathan Mubina; Tsabitha, Naswa Bayu; Soeprapto, Adam Cahya; Hakim, Fauzan (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of ships as transportation vessels has a relatively low accident rate due to the incorporation of prevention and mitigation facilities in ship construction. However, with the increasing demand and variety of ships, the need for electrical energy on board fluctuates significantly. Utilizing ship power generators can harness solar energy as an alternative source of electrical energy. Indonesia's solar energy potential is approximately 4.8 kWh/m2, covering regions across the country. Therefore, the research team aims to develop the KISAT SAKSI (Bright Solar Fishing Boat, Leak Threat Sensor System) energy. Solar energy is abundant near the equator and available throughout the year, except during rainy seasons. Solar energy can be used as an alternative to traditional, increasingly limited, and expensive energy sources. The data contained in this document are derived from publications, manufacturers, relevant government agencies, scientific literature, and other sources. Solar energy utilization as electrical energy can be achieved by installing solar panels on ships. The generated electrical energy can power ship propellers, electrical equipment, be used for ship lighting at night, or serve as a leak detection tool for fishing boats. The utilization of solar power systems can also have positive impacts on fishermen, including enhancing health, economics, environmental sustainability, and fostering independent fishermen.